The taxing implementation of densification: The missed opportunity of the German land value tax; Die steuerliche Umsetzung von Verdichtung: Die versäumte Gelegenheit der deutschen Bodenwertsteuer - Cornelia Roboger (Raumforschung und Raumordnung / Spatial Research and Planning, 2023)
Densification and more efficient use of land are important planning challenges across Europe intended to aid the pursuit of sustainability goals. Property taxation influences land use. It can discourage or incentivize efficient land use. In the international academic debate, the land value tax is considered an effective land policy instrument that can promote more efficient use of land. Germany is currently transforming its property taxation system and has discussed different property tax models in the political decision-making process. This paper explores the political motivations of this reform based on a discourse analysis of plenary sessions and complementary in-depth expert interviews. On the one hand, the empirical findings highlight the experts' positive assessment of the potential of the land value tax for efficient land use and densification. On the other hand, they also show how the potential allocative effects of the land value tax were largely overlooked during the political debates. Instead, discussion centred around distributional aspects of the property tax. It can be shown that despite the great potential for tackling urgent planning issues, policymakers are hesitant to adopt and apply instruments of land policy that intervene in existing private property rights. – – Verdichtung und effizientere Nutzung des Bodens sind europaweit wichtige planerische Herausforderungen, um Nachhaltigkeitszielen gerecht zu werden. Die Grundsteuer beeinflusst die Nutzung des Bodens. Sie kann die effiziente Flächennutzung fördern oder hemmen. In der internationalen akademischen Debatte wird die Bodenwertsteuer als ein wirksames bodenpolitisches Instrument angesehen, das eine effizientere Bodennutzung fördern kann. In Deutschland wird derzeit das Grundsteuersystem reformiert und dazu werden im politischen Entscheidungsprozess verschiedene Grundsteuermodelle diskutiert. In diesem Beitrag werden die politischen Beweggründe für die Entscheidung dieser Reform untersucht auf der Grundlage einer Diskursanalyse von Plenarsitzungsprotokollen und ergänzenden Experteninterviews. Die empirischen Ergebnisse zeigen einerseits die positive Einschätzung der Expertinnen und Experten zum Potenzial der Bodenwertsteuer für eine effiziente Flächennutzung und Verdichtung. Andererseits zeigen sie auch, dass die potenziellen Allokationseffekte der Bodenwertsteuer in der politischen Debatte weitgehend ausgeblendet wurden. Stattdessen konzentrierten sich die politischen Debatten auf Verteilungsaspekte der Grundsteuer. Es kann dargestellt werden, dass die Politik trotz des großen Potenzials für drängende Planungsfragen zögert, bodenpolitische Instrumente zu beschließen und anzuwenden, die in bestehende private Eigentumsrechte eingreifen.
Keywords: 710; densification; Germany; land policy; Land value taxation; legislation; Bodenwertsteuer; Verdichtung; Bodenpolitik; Deutschland; Gesetzgebung